Interventional Radiology for Medical Students (Springer International Publishing, 2018)
This book provides easily accessible technique specific information on interventional radiology (IR) procedures at a basic level for medical students and junior doctors. It covers subject topics in both vascular and non-vascular interventional radiology appropriate for a non-specialist audience. Case based contents help to introduce IR techniques and demonstrate the role of minimally invasive therapy in the overall clinical management. Pre and post-procedural patient assessments are also included in the chapters to enhance patient safety and early detection of complications. Interventional Radiology treatments now play a major role in many disease processes and continues to grow with new procedures added to the armamentarium of the interventional radiologist, almost on a yearly basis. Interventional radiology because of its pivotal role in medical care, requires its own teaching curriculum. Recognising this, the Cardiovascular and Interventional Radiology Society of Europe (CIRSE) devised an undergraduate curriculum in IR, specifically designed for teaching medical students. This book will be primarily of benefit to medical students. In addition, it will also be of help to non-radiology junior hospital doctors and general practitioners.